2001
DOI: 10.1002/1097-4628(20010124)79:4<703::aid-app150>3.3.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Pervaporative permeations of homologous series of alcohol aqueous mixtures through a hydrophilic membrane

Abstract: The permeation behaviors of permeants were investigated in the pervaporation of a homologous series of alcohol aqueous mixtures through a hydrophilic poly(vinyl alcohol) (PVA). The PVA membrane was crosslinked with glutaraldehyde. A homologous series of alcohols used in this study were methanol, ethanol, 1-propanol, and 1-butanol. The pervaporation experiments were carried out with feed having 70 -97 wt % of alcohol contents and at various feed temperatures. In a high alcohol content above 92 wt %, the permeat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…A good pervaporation membrane material should have a high permeation flux and separation factor for the pervaporation dehydration of alcohol. Most studies on pervaporation dehydration of alcohols have focused on highly hydrophilic materials because of their strong affinity to water molecules 12–14. In particular, poly(vinyl alcohol) (PVA) is widely used as a membrane material for the separation of water/ethanol solutions by pervaporation because the PVA membrane shows remarkable selectivity toward water and has excellent film‐forming characteristics with good resistance to organic mixtures, even though it has poor stability in aqueous mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…A good pervaporation membrane material should have a high permeation flux and separation factor for the pervaporation dehydration of alcohol. Most studies on pervaporation dehydration of alcohols have focused on highly hydrophilic materials because of their strong affinity to water molecules 12–14. In particular, poly(vinyl alcohol) (PVA) is widely used as a membrane material for the separation of water/ethanol solutions by pervaporation because the PVA membrane shows remarkable selectivity toward water and has excellent film‐forming characteristics with good resistance to organic mixtures, even though it has poor stability in aqueous mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…Performance of pervaporation is dependent not only on the membranes but also on the operating parameters such as feed composition, temperature, and other factors 11–14. Because the sorption and diffusion of each component are strongly concentration dependent, changing of feed composition will affect the flux and selectivity in pervaporation.…”
Section: Introductionmentioning
confidence: 99%
“…Because the sorption and diffusion of each component are strongly concentration dependent, changing of feed composition will affect the flux and selectivity in pervaporation. Yeom et al12 investigated a homologous series of aqueous alcohol solutions through a poly (vinyl alcohol) (PVA) membrane with various feed compositions and found that the feed composition would directly affect the affinities between feed components and membrane as well as the mutual interactions among the feed components. On the other hand, changing the operating temperature may cause the change of membrane structure and mutual interaction between components, which consequently contribute to the change of the mass transport coefficient of components 13.…”
Section: Introductionmentioning
confidence: 99%
“…This behavior can be attributed to the characteristics of both diffusivity and the solubility. The solubility is a thermodynamic parameter that provides a measure of the amount of penetrant sorbed by the membrane at equilibrium . The permeance of water vapor and N 2 in the mixed gas was positively increased from 191.5 GPU to 731.9 GPU and 1.3 GPU to 16.7 GPU, respectively, with the composition of PEG increasing in the coating solution.…”
Section: Resultsmentioning
confidence: 99%